Evaluating Two Oral Health Video Interventions with Early Head Start Families - Lynn B. Wilson; Barbara DeBaryshe; Malkeet Singh; Sharon Taba (International Journal of Dentistry)
Poor oral health in early childhood can have long-term consequences, and parents often are unaware of the importance of preventive measures for infants and toddlers. Children in rural, low-income families suffer disproportionately from the effects of poor oral health. Participants were 91 parents of infants and toddlers enrolled in Early Head Start (EHS) living in rural Hawai'i, USA. In this quasi-experimental design, EHS home visitors were assigned to use either a didactic or family-centered video with parents they served. Home visitors reviewed short segments of the assigned videos with parents over an eight-week period. Both groups showed significant prepost gains on knowledge and attitudes/behaviors relating to early oral health as well as self-reported changes in family oral health routines at a six-week followup. Controlling for pretest levels, parents in the family-centered video group showed larger changes in attitudes/behaviors at posttest and a higher number of positive changes in family oral health routines at followup. Results suggest that family-centered educational videos are a promising method for providing anticipatory guidance to parents regarding early childhood oral health. Furthermore, establishing partnerships between dental care, early childhood education, and maternal health systems offers a model that broadens potential reach with minimal cost.